Prevalence of syphilis and chlamydia trachomatis infection among female sex workers in Jiangsu, China: Results from a multicenter cross-sectional and venue-based study - Shi, Lingen; Luo, Jun; Chen, Yuheng; Chen, Liping; Hu, Haiyang; Qiu, Tao; Liu, Xiaoyan; Xu, Xiaoqin; Chen, Yunting; Zhang, Zhi; Zhou, Ying; Lu, Jing; et al. (Frontiers in Public Health, 2022)
Background Female sex workers (FSWs) are considered highly vulnerable to sexually transmitted infections (STIs), but available data on the prevalence of STIs among FSWs in China is limited at a provincial level. This study aimed to evaluate the prevalence of STIs and risk factors among FSWs in Jiangsu, China. Methods We conducted a multicenter cross-sectional study in seven cities of Jiangsu to investigate the prevalence and risk factors associated with HIV and other STIs. Blood and urine were collected to test for HIV, syphilis, Hepatitis C (HCV), Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) infections. Results We enrolled 3,580 FSWs. The overall prevalence of bacterial STIs was 6.2% (5.4%−7.0%). The prevalence of HIV, syphilis infection, HCV, NG and CT were 0.1% (95%CI, 0.0–0.2), 1.8% (95%CI, 1.4–2.3), 0.3% (95%CI, 0.1–0.5), 0.3% (95%CI, 0.2–0.5) and 4.3% (95%CI, 3.6–5.0), respectively. Most FSWs (85.6%) reported consistent condom use with clients in the past month. Only 10.6% of FSWs reported group sex, and 68.3% self–reported HIV testing in the previous year. According to the multivariable model, having group sex in the past year (aOR, 2.521, 95%CI: 1.366–4.651) and HIV infection (aOR, 26.260, 95%CI: 2.432–283.563) were associated with a higher risk of syphilis infection. Migrants (aOR, 1.669, 95%CI: 1.163–2.395), having a history of STIs in the past year (aOR, 4.601, 95%CI: 1.003–21.118), and NG infection (aOR, 38.549, 95%CI: 11.214–132.514) were associated with a higher risk of CT infection. On the contrary, FSWs aged older than 25 were associated with lower risk of syphilis infection (25–34: aOR, 0.339, 95%CI: 0.151–0.763) and CT infection (25–34: aOR, 0.503, 95%CI: 0.316–0.802; ≥35: aOR, 0.578, 95%CI: 0.362–0.925). Conclusion This study's prevalence rates of syphilis and CT infections show the need to promote comprehensive STIs control and prevention strategies, including behavioral intervention and STIs screening, especially in younger high–risk populations. With the increasing coverage of HIV testing, integrating other STIs screening with HIV testing may be a reasonable way to implement comprehensive STIs control and prevention.